Eugenio Claudio Di Stefano. The Vanishing Frame: Latin American Culture and Theory in the Postdictatorial Era. U of Texas P, 2018. - Tamara Mitchell (Studies in 20th & 21st Century Literature, 2021)
Review of Eugenio Claudio Di Stefano. The Vanishing Frame: Latin American Culture and Theory in the Postdictatorial Era. U of Texas P, 2018. 185 pp.
Keywords: Southern Cone; Latin America; human rights; aesthetics; post dictatorial literature; identity politics